Hematological Profile of Neonates Born to Mother with Pregnancy Induced Hypertension Presenting at Tertiary Care Hospital - Sania Rafique, Mashal Khan, Mehmood Sheikh, Muhammad Hanif, Maira Riaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The aim of this research is to collate the hematological profile of neonates born to mothers with and without pregnancy induce hypertension. Methodology: A Case-control study was undertaken at the Department of NICU, National institute of child health, Sindh between October 2020 and March 2021. We have evaluated details and full blood count results of neonates born to mother with pregnancy induced hypertension (PIH) in collation with the data of control group. Results: Around of 156 neonates born to mother with gestational hypertension and 156 neonates of healthy pregnant mother were enlisted. Full blood counts showed Hemoglobin (hb) levels were significantly higher in newborns of mothers with pregnancy induced hypertension(16.3+ 0.38) than the control (14.81+ 0.04) (p=0.001). White blood cells (WBSs) were notably reduced in neonates of PIH mothers (9.02±0.64 and 15.41+ 0.8 respectively) (p=0.001). In our study Neutropenia was seen in 42% of neonates born to PIH mothers as compared to 8% in control group. Mean ANC in neonates born to mother to hypertensive disorders of pregnancy (5000) was significantly lower than that of babies born to normotensive mothers (8200) in our study. The platelet count in the case group was notably reduced (138.79±4.52) when compared to the control group, which registered a count of 209.11±15.54. Conclusions: Neonates born to mothers with gestational hypertension are more vulnerable for occurrence of neutropenia, leucopenia, thrombocytopenia and polycythemia. Timely hematological screening assist to reduce morbidity, improve growth, development and survival of the baby. Keywords: Neutropenia, thrombocytopenia, hematology, gestational hypertension, newborn.